Pengaruh Return on Equity, Financial Leverage dan Ukuran Perusahaan Terhadap Underpricing Saham - Angie Auryn Taslim; Indrayenti Indrayenti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The purpose of this study is to discover whether return on equity, financial leverage, and company size are factors that causing stock underpricing. The research was conducted quantitatively. Selection of the sample by using purposive sampling. The data is gained by company financial statement that are undertaking initial public offering in 2019-2021 on Indonesia Stock Exchange. The data accumulated method by using documentation way and 61 company data was obtained. Multiple regression linear test is been used as a method to examine the data. Partial test indicates that return equity and company size have a significant effect on stock underpricing and financial leverage shows the opposite result. Simultaneous test results concluded that return on equity, financial leverage, and company size simultaneously influencing stock underpricing.